RISK COVERAGE IN IMG RENTAL BANDA ACEH BETWEEN THE RENTAL CAR AND THE RENTER IN THE PERSPECTIVE OF IJARAH BI AL-MANFA'AH CONTRACT - Teuku Muttaqin Mansur; Badri Hasan (JURISTA: Jurnal Hukum dan Keadilan, 2020)
Risk coverage is the company's responsibility to customers if something unwanted happens, such as an accident that makes the rental object damaged. This research aims to find out how the legal relationship between the parties in the implementation of the car rental agreement that has been insured and how the rent car risk coverage according to the perspective of Islamic law (Ijarah bi al-Manfa'ah). This research uses the method of case studies, namely direct observation of the object under study simultaneously. The results of the study found that the coverage provided by the rent car to the renter has an element of gharar (fraud), where the renter is required to pay again when the rental object enters the insurance workshop, even though at the beginning of the agreement the renter has paid an insurance claim if one day an accident occurs that can damage the rental object. The rent car company argues that the reason why it is charged again is because the car cannot be operated when it enters the insurance workshop. In Islam, leasing of goods whose objects are benefits is included in the Ijarah bi al-Manfa'ah contract. The IMG rental company has not fulfilled the rules of lease coverage in accordance with Islamic law where there is speculation that requires the renter to pay two payments when the rental object is damaged and enters the insurance workshop.